2017
DOI: 10.14260/jemds/2016/1178
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Stable Intramedullary Nailing of Femoral and Tibial Shaft Fractures in Children

Abstract: BACKGROUND AND OBJECTIVEManagement of femoral and Tibial diaphyseal fractures in the age group of 5-15 years is still controversial between conservative and surgical methods. Compared with young children, this group of children have high risk of malunion and shortening when managed conservatively. Surgical methods are widely used in this age group of children with intramedullary fixation being increasingly preferred. Aim of this prospective study was designed to examine the outcome and complications of Elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A different study from Gujarat found that excellent results occurred in 54% of instances, satisfactory results in 24% of cases, unsatisfactory results in 12% of cases, and failures occurred in 10% of cases [ 14 ]. Ganesan et al also observed excellent results in 50% of the instances, satisfactory results in 30% of the cases, unsatisfactory results in 10% of the cases, and failure results in 10% of the cases [ 15 ]. According to a study by Jagiasi et al, the results were outstanding in 40% of the instances, very good in 6.66%, good in 30%, fair in 20%, and poor in 3.33% of the cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A different study from Gujarat found that excellent results occurred in 54% of instances, satisfactory results in 24% of cases, unsatisfactory results in 12% of cases, and failures occurred in 10% of cases [ 14 ]. Ganesan et al also observed excellent results in 50% of the instances, satisfactory results in 30% of the cases, unsatisfactory results in 10% of the cases, and failure results in 10% of the cases [ 15 ]. According to a study by Jagiasi et al, the results were outstanding in 40% of the instances, very good in 6.66%, good in 30%, fair in 20%, and poor in 3.33% of the cases [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of falling and suffering fractures is very common in children and elderly people. Tibia fractures are the third most frequent long bone fractures in children with 15% occurrence [3], [4]. Considering that fractures in superficial bones are frequent, it would be beneficial to have an alternative non-ionizing and non-invasive screening method, for first response screening in ambulances, retirement houses, pregnant women, newborn, and infants, or in low-income settings.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the tibial shaft fractures are managed conservatively. The indications for the operative treatment include open fractures, neurovascular deficits, polytrauma, unstable fracture patterns, and fractures that fail to meet acceptable reduction parameters (roughly 10 degrees of sagittal angulation, 10 degrees of varus/valgus, >50% translation (2) .…”
Section: Introductionmentioning
confidence: 99%